PENGEMBANGAN SISTEM KASIR PRINT COLOR ANALYSIS PADA PERCETAKAN PENJILIDAN EXPRESS TULUNGAGUNG MENGGUNAKAN FRAMEWORK LARAVEL DENGAN KERANGKA KERJA SCRUM - Lailatul Musyarofa; Yayak Kartika Sari; Joko Iskandar (J-INTECH ( Journal of Information and Technology), 2026)
The manual and subjective process of determining color printing costs and recording sales transactions at Penjilidan Express, which resulted in inconsistent pricing, recording errors, and reduced operational efficiency. This research focuses on developing a web-based cashier system equipped with a Print Color Analysis feature to support more objective and consistent printing cost estimation and streamline transaction management. The system was developed using the Scrum framework and implemented with the Laravel framework based on the Model-View-Controller (MVC) architecture. The Print Color Analysis feature calculates the percentage of RGB/CMYK color composition from digital files in JPG, PNG, and PDF formats to automatically estimate printing costs. The developed system was evaluated through Black Box Testing across seven core functional features. The results demonstrated that every tested feature performed as expected, achieving a 100% success rate and confirming that the system fulfilled all predefined functional requirements.The developed system is expected to improve the consistency of printing cost calculations, streamline transaction processing, and minimize the risk of errors in sales data recording. Therefore, the proposed system can serve as an effective solution to support operational efficiency, pricing transparency, and business digitalization in printing service companies.